Gwarowe frazeologizmy określające wiek człowieka (na przykładzie materiału śląskiego) - Przymuszała, Lidia (Słowiańska frazeologia gwarowa II, 2020)
DIALECTAL IDIOMS DETERMINING THE AGE OF THE HUMAN BEING (BASED ON THE MATERIAL OF THE SILESIAN)The article contains a semantic and formal analysis of a selected group of phraseological compounds (collected 150 units) recorded in Silesian dialects and talking about the human age. The collected phraseologies creating a thematic field of general importance AGE AND STAGES OF HUMAN LIFE are divided and characterized within five sub-fields: Childhood, Early youth, Maturity, The process of growing old / Senility and Death. The phraseology of the discussed field is characterized by big imagination, negative evaluation, strong expressive features, multi meaning and semantic blur.